Pemanfaatan Media Pembelajaran Lectora Inspire Dalam Upaya Peningkatan Kualitas Pembelajaran (Pengabdian Masyarakat di SLTPN 7 Kota Payakumbuh) - Elvi Rahmi; Efni Cerya (Universitas Negeri Padang, 2020)
A qualify learning process that is fullfill the needs of students is urgent for a teacher, so that the expected learning objectives can be achieved. Implementation of multi-media in learning is one of alternative method. Lectora inspire is a program that can be used by teachers in designing multi-media learning. Lectora inspire can be used to combine flash, record video, combine images and screen capture. Lectora Inspire has the advantage of being user friendly, because it does not require understanding of complex programming languages. The design and manufacture of multi- media using the Lectora Inspire program is carried out by providing integrated training to teachers of SLTPN 7 Payakumbuh City. Training methods are provided by providing information, discussion, guided practice, independent practice and ending with evaluation.Keywords : media, instructional, lectora inspire